IMPLEMENTASI GERAKAN LITERASI SEKOLAH MELALUI PROGRAM POJOK BACA SISWA KELAS IV B SD NEGERI 1 PENATIH - Ni Made Oktaviani; Ni Nyoman Perni; Ni Nyoman Tri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Literacy is the ability to read, write, and communicate within the context of society, language, culture, and social relationships related to knowledge. At the elementary school level, literacy development forms the foundation for students' learning. The School Literacy Movement (GLS) engages the whole school community students, teachers, principals, education staff, supervisors, committees, mass media, and the local community. This study specifically examines the implementation of the School Literacy Movement through the reading corner program for grade IV B students at SD Negeri 1 Penatih, describing challenges and outcomes. This descriptive qualitative study involved teachers, grade IV B students, and the principal, focusing on the School Literacy Movement through reading corners. Data collection used triangulation: observation, interviews, and documentation. The study, conducted at SD Negeri 1 Penatih, found that each classroom has a reading corner at the back, which positively impacts class IV B students' reading interest and supports literacy activities.